Influence modern fitness of the systems on motivation to employments of physical culture of teenagers of task medical force - Георгієва [Nadezhda Georgieva], Надія Георгієвна (Slobozhanskyi Herald of Science and Sport, 2013)
The aim of the paper is to explore the influence of contemporary fitness-systems on formation of motivation towards physical training in the process of students' physical education. During the last few years the interest towards physical training has decreased and the number of children making part of preparatory and special medical groups has risen. Taking this into account, it was suggested to use contemporary fitness-systems in the process of physical education of children of the special medical group in order to increase their interest and motivation towards physical training. The positive effect in formation of educational motivation, in reduction of common school anxiety, in growth of success-orientation has been proved.